Impact of different crop establishment methods on yield attributes, yields and economics of rice: A comparative study - Padma, Sayam; Vijayakumar, S; Venkatanna, B; Srinivas, D; Kumar, R Mahender; Kuchi, Surekha; Mahadevappa, SG; Sundaram, Raman Meenakshi; Rekha, K Bhanu; Yakadri, M (ORYZA-An International Journal of Rice, 2023)
A field study was conducted during the kharif season of 2022 to investigate the effect of different rice production systems on yield attributes, crop yields and economics. The experiment was laid in randomized block design with three replications, encompassing seven treatments. Three treatments involved transplanting methods viz., system of rice intensification (SRI), mechanical transplanting and conventional transplanting. The remaining four treatments were direct seeded rice (DSR) treatments viz., wet DSR (drum seeding), wet DSR (broadcasting), dry converted wet rice (broadcasting) and dry converted wet rice (line sowing). The results showed that the yield attributes viz. panicles m-2, panicle length and weight, filled grains panicle-1, fertility percentage and grain yield were significantly higher in wet DSR (drum seeding) followed by dry converted wet rice (line sowing), SRI method. In terms of economic analysis, wet DSR (drum seeding) exhibited the highest gross returns, net returns and benefit-cost ratio (B:C ratio). On the other hand, the dry converted wet rice (broadcasting) method showcased the lowest yield attributes, grain yield, net returns, and B:C ratio among all the crop establishment methods. Based on the findings, it is recommended to adopt either wet DSR (drum seeding), dry converted wet rice (line sowing) and SRI method during the kharif season to achieve maximum yield and economic returns.